COVID-19 Drug Development Recent Advances, New Perspectives and Applications - Aditya Parikesit, Arli (IntechOpen, 2022)
COVID-19 is a rampant worldwide problem. It is caused by the SARS-CoV-2 virus and is manifest in different variants. The Delta variant compromised existing therapeutic and preventive options for this disease and is beginning to be replaced by the Omicron variant. Through pharmaceutical biotechnology, three different treatment approaches to COVID-19 have been developed: computer-aided drug design (CADD); rational drug design in the wet lab; and the advanced drug delivery system. These approaches are heavily influenced by advances in life sciences, such as the development of structural bioinformatics, the establishment of nanobiotechnology as a standard approach in drug design, and major advances in structural biology such as the development of the CryoEM method. This book will focus on providing possible solutions to the ongoing COVID-19 pandemic in light of these advances in life sciences.